ҚАҲАРМАНЛЫҚ ДӘСТАНЛАР ПОЭТИКАСЫ – ҚАБЫЛ МАҚСЕТОВ ИЗЕРТЛЕЎЛЕРИНДЕ - Сарсенбаева, А.К. (FAN va JAMIYAT, 2025)
The article analyzes the monographic research of the renowned folklorist, professor K.Maksetov, dedicated to the poetics of Karakalpak heroic epics in the 1960s. The scholar's first scientific and theoretical views are discussed on the poetics of Karakalpak heroic epics.